2013
DOI: 10.1007/s15010-013-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for late presentation in a cohort of HIV-infected patients in Dresden: positive serology for syphilis in MSM is a determinant for earlier HIV diagnosis

Abstract: A positive syphilis screening test seems to be a determinant for lower risk of late presentation to HIV care and diagnosis in MSM. The presence and awareness of sexually transmitted infections (STIs) such as syphilis may lead to earlier utilisation of HIV health care and, thus, promote earlier HIV diagnosis. HIV prevention strategies should focus more on STIs and not only on HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
2
4
0
4
Order By: Relevance
“…Since current data indicates that STI predominantly circulate among HIV infected men with increased risk behavior, international and German recommendations have been developed promoting intensified STI screening in this particular patient population. In this context, diagnosis of an STI may thus contribute to the early diagnosis of an HIV infection: in our patient group, HIV positive MSM with a positive syphilis serology showed a lower risk for late presentation of HIV . This has also been the case in a Korean study in MSM with a positive VDRL test as marker for active syphilis .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Since current data indicates that STI predominantly circulate among HIV infected men with increased risk behavior, international and German recommendations have been developed promoting intensified STI screening in this particular patient population. In this context, diagnosis of an STI may thus contribute to the early diagnosis of an HIV infection: in our patient group, HIV positive MSM with a positive syphilis serology showed a lower risk for late presentation of HIV . This has also been the case in a Korean study in MSM with a positive VDRL test as marker for active syphilis .…”
Section: Discussionsupporting
confidence: 70%
“…The percentage of late presenters, i.e. primary HIV diagnosis with a CD4 count of <350/μl by definition , in a previous analysis of our patient group largely matched national figures at 50 % . According to current guidelines, CD4 counts <350/μl in asymptomatic patients constitute an indication for antiretroviral therapy (ART).…”
Section: Discussionsupporting
confidence: 66%
“…As mentioned above, and in accordance with previous reports [27][28][29][30], our findings confirm that migrants are much more likely to receive care at advanced stage, with about 55 and 35 % of them, respectively, classified as late presenters and very late presenters. In our study, patients belonging to these categories showed a more advanced age and a risky heterosexual behaviour, suggesting a lower risk awareness both in Italian and migrant population [31]. Moreover, among the latter, illegal status plays an important role in enhancing delay in access, which strongly highlights the need to facilitate early access to health services as much as possible, also for public health implications.…”
Section: Discussionmentioning
confidence: 60%
“…The presence and awareness of syphilis may lead to earlier utilisation of health care (Spornraft-Ragaller et al ., 2013), thereby preventing other STIs, including HIV. Earlier utilisation of health care benefits not only donors but also their partners, children and society (de Almeida Neto et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%